MANAJEMEN SUPERVISI PENDIDIKAN DI PESANTREN TERPADU NURUL IMAN COT GIREK: MEMBENTUK GENERASI MUDA BERKARAKTER ISLAM - Suriani, Ima; Yusrianti, Susi (Jurnal Dedikasi Pendidikan, 2025)
PThis research examines the management of educational supervision at Pesantren Terpadu Nurul Iman Cot Girek with the primary goal of shaping a strong Islamic character among the younger generation. Through a qualitative approach, the study explores the educational supervision practices at the pesantren, investigating how these practices influence the formation of Islamic character in the younger generation. Data were obtained through participatory observation, interviews, and document analysis. The findings highlight the role of supervision in directing the educational process towards achieving the goal of forming an Islamic character, including oversight of the curriculum, teaching methods, and student personality development. The practical implications of this research can serve as a foundation for the development of more effective policies and practices in pesantren and other Islamic educational institutions, potentially leading to positive impacts on the formation of Islamic character in the younger generation. Thus, this research not only contributes academically to understanding educational supervision management in pesantren environments but also provides practical guidance for pesantren administrators and stakeholders in designing strategies to enhance the effectiveness of Islamic education. Through the application of the research findings and recommendations, it is hoped that pesantren and other Islamic educational institutions can be more successful in their mission to shape a strong character in the younger generation, based on deep Islamic values